Handbook of mechanical nanostructuring - Aliofkhazraei, Mahmood (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co. KGaA, 2015)
The nanostructuring of materials is a versatile route particularly well-suited to the fabrication of metallic materials for engineering applications with desired properties, for example, increased corrosion and temperature resistance, enhanced performance under mechanical loads or the long-term shape preservation of workpieces. This ready reference provides in-depth information on both the bottom-up and the top-down approaches to the synthesis and processing of nanostructured materials. The focus is on advanced methods of mechanical nanostructuring, such as severe plastic deformation, includin.
5.1.3 Atomic Force Microscopy5.2 Applications of Optical Microscopy and AFM; 5.2.1 Applications of Optical Microscopy; 5.2.2 Applications of Atomic Force Microscopy; 5.3 New Developments of Optical Microscopy and AFM Techniques; 5.3.1 Optical Microscopy-Based 3D Shape Reconstruction; 5.3.1.1 Defocus Imaging Model; 5.3.1.2 New Shape Reconstruction Method; 5.3.1.3 Experimental Results; 5.3.2 AFM Based Elasticity Imaging and Height Compensation Method; 5.3.2.1 Compression Effect; 5.3.2.2 Surface Characteristics Measurement; 5.3.2.3 Experiments with MWCNTs and Graphenes; 5.4 Conclusion.
Includes bibliographical references and index.
Print version record.
Keywords: Nanostructured materials; Nanostructures; Nanostructured materials; Nanostructures; Nanotechnology; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Nanostructured materials; Nanostructures; Electronic books; Electronic books